Effect of cellular protein kinases blockade on the s100 retina expression in experimental diabetic retinopathy - K. O. Usenko; S. O. Rykov; O. O. Dyadyk; S. V. Ziablitsev (Patologìâ)
The positive effect of cellular protein kinases blockade in diabetes and diabetic retinopathy (DR) justifies the need to clarify molecular mechanisms, among which the trigger regulatory role belongs to calcium-binding proteins S100.